Perbedaan gender dalam pengaruh media sosial terhadap overweight dan obesitas pada remaja: Scoping Review - Delto Loisandro Tanesab; Muhammad Farmawy (DAPU Aceh Publishing, 2025)
Overweight and obesity in adolescents are global public health challenges, including in Indonesia. These conditions are associated with various physical and mental health risks, such as type 2 diabetes, cardiovascular disease, low self-esteem, and depression. As the use of social media among adolescents increases, so does concern about its impact on eating behavior, physical activity, and body perception. However, understanding of how social media influences adolescents' nutritional status based on gender remains limited. This study is a scoping review aimed at mapping the scientific evidence related to the influence of social media use on overweight and obesity in adolescents, taking gender differences into account. Literature searches were conducted through the PubMed and Scopus databases, yielding 650 articles, with five studies meeting the inclusion criteria. The review results showed that social media use is correlated with increased BMI in both male and female adolescents through different mechanisms. In females, social pressure and cyberbullying contribute to unhealthy eating patterns. Meanwhile, in males, high social media use is associated with insufficient sleep and a sedentary lifestyle. Other sedentary activities such as watching TV and playing video games further exacerbate the risk of obesity. These findings emphasize the importance of a gender-based approach in obesity prevention interventions for adolescents in the digital era.